High utilization of inpatient detoxification: predictors among US veterans. (3rd May 2016) - Chang, Grace; Raffi, Edwin; Tang, Michael; Fernando, Gerard I.; Zucker, Jarred; Schein, Abigail Z.
ABSTRACT: Background : Readmissions are among the most problematic and expensive problems in the treatment of substance use disorders. Objective : To evaluate the characteristics associated with four or more inpatient medically managed detoxification admissions in FY 2012, when all had post-discharge appointments within 7 days. Methods : A retrospective case control study. A total of 38 (6.0%) of 623 unique veterans had four or more detoxification admissions (high utilizers). A random sample of 42 was selected from the remaining 585 people (comparison group). In all, 264 detoxification and 70 hospital admissions for other reasons were reviewed. Results : The high utilizers had more alcohol use disorder (AUD, 82% versus 59%, p = 0.03) of significantly longer duration (mean 28.9 years [SD = 17] vs. 19.6 [SD = 13.4], p = 0.01). AUD increased the odds of being a high utilizer three-fold [OR = 3.0, 95% CI 1.1, 8.4], and every additional year of AUD, increased the number of admissions 1.3%, p = 0.0006. The high utilizers did not differ from the comparison group with regards to either number of hospitalizations for other reasons (mean 1.2 [SD = 1.9] vs. 0.57 [SD = 0.8], p = 0.06) or rate of 7 day post discharge appointments kept (46.9% vs. 49.3%, p = 0.82). Conclusions : High utilizers were a small percentage of patients (6.0%) who accounted for a disproportionate number (23%) of 977 detoxification admissions. They had greater disease severity as manifest by more years of AUD. They were not more likely to have hospitalizations for other reasons or less likely to keep post discharge appointments. These patients may warrant different services tailored to prevent hospital readmissions for detoxification.